Steering on Degrees of Freedom of 2D Van der Waals Heterostructures. Issue 1 (13th October 2021) - Zhang, Hui-Zhen; Wu, Wen-Jing; Zhou, Lin; Wu, Zhen; Zhu, Jia
Abstract : 2D heterostructures have garnered tremendous attention for potential applications in electronics and optoelectronics. Heterostructures can be constructed by assembling individual atomically thin layers of 2D materials into integrated devices, which involves three primary degrees of freedom (DOFs), i.e., Lego‐like basic building blocks, out‐of‐plane stacking order, and in‐plane twist‐angle alignment. By steering the DOFs of 2D materials, devices and structures such as artificial Shockley junction, quantum wells, and superlattices can be conveniently established based on well‐developed fabrication and/or assembly techniques, beneficial for next‐generation ultracompact information technologies. Herein, the recent progress on constructing the artificial atomic structures by taking advantage of three primary DOFs is overviewed. An outlook of the challenges and future developments is presented as well. Future advancements in the rational construction of complex devices and artificial heterostructures are also suggested. Abstract : 2D atomic crystal materials are most attractive candidates for next‐generation optoelectronics because of their unique mechanical, electronic, and optical properties. Extraordinarily, the heterogeneous assembly of 2D material structures has evidenced plenty of intriguing physical properties. From the viewpoint of the precise fabrication, this review summarizes the most important degrees of freedom and their potential figures of merit. Finally, the review provides a future perspective on the artificial heterostructures of 2D atomic crystals.